Enhancing MSMEs Business Performance Using Behavioral Intention and Use Social Media Marketing: The Moderating Role of Resistance to Change - Rihan Hafizni; Ratni Prima Lita; Yulia Hendri Yeni; Syafrizal (Management Analysis Journal, 2024)
This study aims to enhancing msmes business performance using behavioral intention and use social media marketing with the moderating role of resistance to change. Social media marketing is a strategic factor in business performance. Behavioral intention and use social media marketing have received special attention in the context of use social media marketing due to its important role in enhancing business performance. This study used a survey method with 300 respondents. For analyzing  the data using Smart-PLS (Partial Least Square) for Structural Equation Modelling (SEM). The results show that behavioral intention positively affect on use social media marketing and use social media marketing positively affects on employee performance. Furthermore, resistance to change acts as a negatively moderation between the relation behavioral intention on use social media marketing them. This research provides further suggestions on how behavioral intention can improve use social media marketing and enhancing business performance in their working area.